Pedro Fernandez de Castro, Count of Lemos VII and their parcels in Huaylas-Ancash - Cajavilca Navarro, Luis (2013)
The research is about the life and property in the Viceroyalty of Peru of Pedro Fernandez de Castro Andrade and Portugal; VII Count of Lemos, Marquis of Sarria IV, V Count of Villalba, III of Andrade and Great of Spain First Class. “The great Count of Lemos”, Indian Council President, Viceroy of Napoles, President of the Supreme Council of Italy, commander of the Order of Alcántara and famous Spanish statesman and diplomat. Rome Ambassador Extraordinary and Kingdom of Galiciasheriff. Temporarily research is located in the second half of the sixteenth century and the first half of the seventeenth century and was concerned primarily with uncovering a part of our history, referring to the provisions of King Philip III who by royal decree on 17 December 1607, made thanks to these gentlemen Count and Countess of Lemos for the life of the two parcels on Indian allotments “cows”. The divisions that were identified and charged were: Huaylas, Marca, Huaras, the Cupirpango term of Cusco, Azángaro and cayo Aymara, district Huamanga and to manage the mills of Huaraz, Carhuas and San Gregorio in distribution of Marca; Collana of Lampas in the province of Cajatambo